2012
DOI: 10.1016/j.jalz.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid imaging in dementias with atypical presentation

Abstract: We explored the potential value of amyloid imaging in patients with atypical presentations of dementia. Twenty-eight patients with atypical dementia underwent PET imaging with the amyloid imaging tracer Pittsburgh Compound-B (PiB). Twenty-six had [18F]fluoro-2-deoxy-D-glucose (FDG) PET scans. After extensive clinical evaluation, this group of patients generated considerable diagnostic uncertainty and received working diagnoses that included possible AD (pAD), focal dementias [e.g. posterior cortical atrophy (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…29,40 On the other hand, 3 of these 8 patients and the 7 patients with CD and DLB suspicion showed PIB retention, confirming that β-amyloid can be also present in other dementias not AD related. 41 Often, this kind of patients may have comorbidities or a mix of neurological pathologies in which the amyloid deposition can be unspecific, and 11 C-PIB may bind to neuritic plaques regardless the pathology. Of course, in this context, a negative 11 C-PIB has the greatest value.…”
Section: Discussionmentioning
confidence: 99%
“…29,40 On the other hand, 3 of these 8 patients and the 7 patients with CD and DLB suspicion showed PIB retention, confirming that β-amyloid can be also present in other dementias not AD related. 41 Often, this kind of patients may have comorbidities or a mix of neurological pathologies in which the amyloid deposition can be unspecific, and 11 C-PIB may bind to neuritic plaques regardless the pathology. Of course, in this context, a negative 11 C-PIB has the greatest value.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies of typical and atypical clinical presentations of Alzheimer's disease, there has been a dissociation between the rather diffuse distribution of amyloid-b plaques and the highly specific patterns of neurodegeneration that strongly correlate with symptomatology (Rabinovici et al, 2010;Wolk et al, 2012;Lehmann et al, 2013;Jung et al, 2015). It has often been suggested that tau pathology, rather than amyloid-b, may be driving disease manifestation (Desikan et al, 2012;Jack and Holtzman, 2013).…”
Section: Distinct Variants Of Alzheimer's Diseasementioning
confidence: 98%
“…Among many other applications, amyloid-b imaging has been incorporated into diagnostic criteria for various stages of the disease (Albert et al, 2011;McKhann et al, 2011;Sperling et al, 2011;Dubois et al, 2014), has substantial impact on clinical decision-making (Ossenkoppele et al, 2013a;Sanchez-Juan et al, 2014) and patient management plans (Schipke et al, 2012;Grundman et al, 2013), and has shown potential as a surrogate outcome measure in clinical trials tailored to reduce cerebral amyloid-b plaque burden (Salloway et al, 2014;Liu et al, 2015). A yet unresolved issue after a decade of amyloid-b imaging research, however, is the disconnection between the diffuse distribution of amyloid-b pathology throughout the neocortex (Rabinovici et al, 2010;Wolk et al, 2012;Lehmann et al, 2013;Jung et al, 2015) and the selective patterns of brain atrophy and glucose hypometabolism that strongly correlate with clinical symptoms (Rabinovici et al, 2010;Ridgway et al, 2012;Lehmann et al, 2013;Madhavan et al, 2013). Thus, although amyloid-b deposition may be a prerequisite to developing Alzheimer's disease dementia, at some point during the disease course additional factors are likely involved in determining regional neurodegeneration and symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, whereas structural (MRI) imaging has emphasized mesial temporal (e.g., hippocampal) atrophy (see above), FDG-PET scanning shows hypometabolism in the lateral temporoparietal and medial parietal cortex, including the precuneus and posterior cingulate gyrus (3,105). It is now possible to study a living brain using all of these modalities and to integrate or coregister the resultant data and correlate them with CSF markers (110)(111)(112)(113)(114). Much of this work has been accomplished through the Alzheimer Disease Neuroimaging Initiative (ADNI), a multicenter, multidisciplinary investigation charged with studying large numbers of subjects with early AD or MCI and comparing them with normal controls (110).…”
Section: Figure 10mentioning
confidence: 99%